Knock Down of Plakophilin 2 Downregulates miR-184 Through CpG Hypermethylation and Suppression of the E2F1 Pathway and Leads to Enhanced Adipogenesis In Vitro - Gurha, Priyatansh (Circ Res, 2016)
RATIONALE: PKP2, encoding plakophilin 2 (PKP2), is the most common causal gene for arrhythmogenic cardiomyopathy (AC). OBJECTIVE: To characterize miRNAs expression profile in PKP2-deficient cells METHODS AND RESULTS: Control and PKP2-knock down HL-1 (HL-1(Pkp2-shRNA)) cells were screened for 750 miRNAs using low-density microfluidic panels. Fifty-nine miRNAs were differentially expressed. MiR-184 was the most down-regulated miRNA. Expression of miR-184 in the heart and cardiac myocyte was developmentally downregulated and was low in mature myocytes. MicroRNA-184 was predominantly expressed in cardiac mesenchymal progenitor cells (MPCs). Knock down of Pkp2 in cardiac MPCs also reduced miR-184 levels. Expression of miR-184 was transcriptionally regulated by the E2F1 pathway, which was suppressed in PKP2-deficient cells. Activation of E2F1, upon over-expression of its activator CCND1 or knock down of its inhibitor RB1, partially rescued miR-184 levels. In addition, DNMT1 was recruited to the promoter region of miR-184 and the CpG sites at the upstream region of miR-184 were hypermethylated. Treatment with 5-aza-2’-deoxycytidine, a demethylation agent, and knock down of DNMT1 partially rescued miR-184 level. Pathway analysis of paired miR-184:mRNA targets identified cell proliferation, differentiation, and death as the main affected biological processes. Knock down of miR-184 in HL-1 cells and MPCs induced and conversely, its over-expression attenuated adipogenesis. CONCLUSIONS: PKP2 deficiency leads to suppression of the E2F1 pathway and hypermethylation of the CpG sites at miR-184 promoter, resulting in downregulation of miR-184 levels. Suppression of miR-184 enhances and its activation attenuates adipogenesis in vitro. Thus, miR-184 contributes to the pathogenesis of adipogenesis in PKP2-deficient cells.